Analisis promosi dan fasilitas dalam meningkatkan minat beli pelanggan di Cafe Pojok Canda - Syahputra, Rizky Indra; Permata, Widiana Indah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2026)
This study aims to determine the effectiveness of promotions and facilities in increasing customer purchase intention at Pojok Canda Cafe. This study used qualitative methods, conducting customer interviews and observations within the Pojok Canda Cafe environment. This study showed positive and significant results from promotions and facilities in increasing customer purchase intention at Pojok Canda Cafe. Furthermore, this study found that training significantly impacted customer purchase intention. Based on these results, it can be concluded that the hypothesis is supported.